Effect of COVID-19 isolation measures on physical activity of children and their parents, and role of the family environment: a cross-sectional study - Amagliani, G.; Baldelli, G.; Italiano, P.; Frisina, P.; Schiavano, G. F.; Brandi, G.; De Santi, M. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The rigorous isolation measures due to the COVID-19 pandemic seriously impacted children’s lifestyles. A descriptive cross-sectional study was carried out to collect and analyze information about physical activity habits of children and their parents during the social distancing period resulting from the COVID-19 pandemic. Methods. An online questionnaire was administered to 363 families (507 children aged 5-13) recruited by convenience sampling, asking for physical activity type and frequency before, during, and after the lockdown period (9th March - May 3rd 2020), education, outdoor spaces, and children’s weight gain perception. Results. Results show a remarkable decrease in children’s physical activity during lockdown (88.9 vs 39.8% active children) associated with older age and low availability of outdoor spaces (p<0.001). Parents’ physical activity was related to educational level, and a slight but significant correlation between parents’ education and children’s physical activity was found, especially with father’s university degree (p<0.05). Active mothers significantly influenced children’s physical activity during the lockdown, especially if not engaged in smart working. The return to an active lifestyle by children did not reach previous levels (75.9% active children) and was directly related to parent’s physical activity. Finally, the risk of weight gain was lower in active children during the lockdown (OR = 0.46; p<0.001). Conclusions. This work highlights the importance of physical activity during a pandemic event to prevent the risk of gaining weight, and underlines the relevance of the entire family system as a source of promotion of healthy behaviors in children.